Women's Actualization in Batikization in the Penginyongan Area as an Effort to Explore Islamic Values - Maftuchah Farichatul; Hidayat Arif (Indonesian Academy of Social and Religious Research (IASRR), 2025)
This study examines the role of women in the batik-making tradition of the Penginyongan region, aiming to reveal the underlying Islamic values embedded within this cultural practice. Gender-based and drawing on cultural studies, this interdisciplinary research emphasizes that women's involvement in batik is not just a routine activity but an integral part of their artistic and spiritual expression. The findings of this study reveal that the actualization of women in batik-making in the Penginyongan area, as a way to explore Islamic values, manifests in two main aspects. First, the Divine value in batik, where the act of making batik is seen as a form of worship, bringing the artisans closer to God. The process of creating batik, accompanied by prayer (wirid), embodies the belief that work itself can be a form of devotion, with prayer serving as nourishment that enhances the work. Second, the Human value in batik is reflected in the perseverance and appreciation for beauty embedded in the craft. The traditional techniques passed down through generations reflect local wisdom, with the use of natural materials for coloring and the motifs drawn in the batik symbolizing values of wisdom, harmony, and simplicity.